Tacrolimus vs. cyclosporine eyedrops in severe cyclosporine‐resistant vernal keratoconjunctivitis: A randomized, comparative, double‐blind, crossover study. Issue 3 (May 2015) - Pucci, Neri; Caputo, Roberto; di Grande, Laura; de Libero, Cinzia; Mori, Francesca; Barni, Simona; di Simone, Lorena; Calvani, Annamaria; Rusconi, Franca; Novembre, Elio
Abstract: Background: Vernal keratoconjunctivitis (VKC) is a chronic sight‐threatening ocular disease. Topical cyclosporine A (Cyc) has been widely administered as a steroid‐sparing drug, although in about 7–10% of cases, it has been ineffective. The purpose of this study was to evaluate the efficacy of 0.1% topical tacrolimus (Tcr) in patients with severe VKC who failed to respond to 1% Cyc eyedrops. Methods: Consecutive patients with severe, Cyc‐resistant VKC were enrolled in a double‐blind, comparative, crossover (DBCO) trial; all patients were treated with 1% Cyc in one eye and 0.1% Tcr in the other eye for 3 wk. After a washout period of 7 days, patients were instructed to cross over the medications for three additional weeks. Objective ocular score, subjective score, and quality‐of‐life questionnaires (QoLQ) were collected during the trial. Blood samples were drawn to assess several safety parameters. Results: Thirty patients have been enrolled (mean age 9.05 ± 2.12 yr). In each of the two phases of the DBCO trial, a significant improvement in objective and subjective scores was observed in the eyes treated with 0.1% Tcr (p < 0.001). Likewise, the quality of life significantly improved despite only half the eyes being successfully treated. Serum creatinine and blood parameters were constantly within the normal range, and both blood Cyc and Tcr concentrations remained below the lowest detectable levels. Conclusions: Topical Tcr is very effective and safe in the short term for patients suffering from severe VKC resistant to topical Cyc. Abstract :